2016
DOI: 10.1038/cti.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF signalling blockade and chemotherapeutic agents act in concert to inhibit the function of myeloid‐derived suppressor cells in vitro

Abstract: Immune evasion is a recently defined hallmark of cancer, and immunotherapeutic approaches that stimulate an immune response to tumours are gaining recognition. However tumours may evade the immune response and resist immune-targeted treatment by promoting an immune-suppressive environment and stimulating the differentiation or recruitment of immunosuppressive cells. Myeloid-derived suppressor cells (MDSC) have been identified in a range of cancers and are often associated with tumour progression and poor patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…19,20 In addition, GM-CSF blockade was able to abolish the immunosuppressive features of human MDSCs in vitro, highlighting GM-CSF as one of the main regulators of MDSC expansion. 21…”
Section: Expansion and Recruitment Of Mdscsmentioning
confidence: 99%
“…19,20 In addition, GM-CSF blockade was able to abolish the immunosuppressive features of human MDSCs in vitro, highlighting GM-CSF as one of the main regulators of MDSC expansion. 21…”
Section: Expansion and Recruitment Of Mdscsmentioning
confidence: 99%
“…Recent studies have reported that in the animal model of endometriosis, chemokines CCL1/2/5 promote the migration of CXCR2 + MDSC to heterotopic grafts, performing immunosuppressive function . GM‐CSF is an important one released by tumor cells, which can promote the proliferation of MDSCs, while G‐CSF can affect the migration of MDSCs probably by upregulating the expression of Bv8, a surface protein on MDSCs . In animal models of colorectal cancer, CXCR2 influences MDSCs migration and recruitment toward tumors by up‐regulating chemotactic factors CXCL1 and CXCL2 .…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 99%
“…Increased production of granulocyte macrophage colony-stimulating factor (GM-CSF) has been observed in the mucosa of patients with inflammatory bowel disease and rodents subjected to experimental colitis. GM-CSF was also shown to promote the generation of myeloid-derived suppressor cells (19). We cultured bone marrow neutrophils from WT or Tollip -/mice in GM-CSF overnight, and subsequently cocultured with CFSE-labeled allogeneic splenocytes in anti-CD3-coated plates.…”
Section: Resultsmentioning
confidence: 99%